'Clio inauguratie (begin cursus '98/99)'. Tweede van rechts zittend met kin naar voren Adama van Scheltema - Schuitvlot, Nic., (1898)
'Clio inauguratie (begin cursus '98/99)'. Tweede van rechts zittend met kin naar voren Adama van Scheltema.